PEMILIHAN E-MAGAZINE TERHADAP KEBUTUHAN DAN KEINGINAN READERSHIP DENGAN MENGGUNAKAN ANALYTIC HIERARCHICAL PROCESS - Akmaludin, Akmaludin (LPPM Universitas Nusa Mandiri, 2013)
Used of the Internet technology superbly proven to not give huge benefits to users, both in terms of deployment and exchange of information, entertainment, freeware software, even to the readings in various forms especially a lot of readings that can be obtained through online channels by the internet without having to purchase in the form of free as well be articles, newspapers, books, and magazines are all in electronic form and can be obtained by the internet. Until recently published magazine in print already behind, because so many turned to the magazine in electronic or digital form is called the e-magazine. With the existence of an intermediate stage in the form of an e-magazine needs assessment of the readership to choose the best performance of any e-magazine published, even many technologies that can support progress towards processing features such as e-magazine like 3D Thumbnails, Podcasts, and RSS. Assessment of the e-magazine readership seen from the goal, multicriteria, and alternative, while the method used is the Analytic Hierarchical Process (AHP). The process of analysis set forth in the acquisition phase synthesize the results of alternative priority e-magazine is e-the largest environmental gain with the value of 0.488 points, followed by RSC studio with acquisition value 0.284, and the smallest synthesize the results obtained e-magazine aksarayana the value 0.229. While the results of the ranking criteria biggest readership want and needs are the ease with criteria further value 0.270 0.235 interfaces with value, quality value 0.179, satisfaction with the value of 0.175, and the smallest are the benefit criteria with a value of 0.142.